Pengaruh kompensasi, Stres Kerja dan Iklim Organisasi Terhadap Kinerja Karyawan Pada PT Cladtek BiMetal Manufactuing Batam - Rosella LumbanTobing; David Humala Sitorus (Komunitas Dosen Indonesia, 2023)
Human resources (HR) is one of the most important factors in a company that is used to drive other resource activities in running a company. Human resources (HR) have a fairly important position because they have a major role in company activities. PT Cladtek Bi Metal Manufacturing is a company engaged in industrial services for several jobs regarding metal materials, especially the Weld Overlay and Lining processes on carbon steel pipes aimed at industry. Compensation can motivate employees to improve work performance and compensation can also be a tool to provide or increase morale in workers. In terms of compensation at PT Cladtek Bi Metal Manufacturing, there are still some employees who feel that the compensation provided has not fully achieved the satisfaction felt by their employees. Likewise with the incident that occurred at PT Cladtek BiMetal Manufacturing, there were many employees who did not work optimally, this happened because in the assignment of very many responsibilities and also the work received was not in accordance with the field mastered, work deadlines, relationships between colleagues the work is not good and the work done is not in accordance with their abilities. The purpose of this is to determine whether compensation, work stress and organizational climate affect employee performance at PT Cladtek biMetal Manufacturing Batam. The method of data collection is through the distribution of questionnaires with a sample of 200 respondents. The type of research used by the researcher in this research is quantitative research with associative nature of research.